Associations of Sex Hormones and Anthropometry with the Speaking Voice Profile in the Adult General Population. - Jost, L.; Fuchs, M.; Loeffler, M.; Thiery, J.; Kratzsch, J.; Berger, T.; Engel, C. (J Voice, 2018)
OBJECTIVE: There is evidence that sexual hormone concentrations and anthropometric factors influence the human voice. The goal of this study was to investigate to what extent body mass index (BMI), body height, body weight, breast-to-abdomen-ratio, testosterone, estradiol, dehydroepiandrosterone-sulfate (DHEA-S), follicle-stimulating hormone, and luteinizing hormone are associated with the sound pressure level and the fundamental frequency of the speaking voice in a cross-sectional approach among adults in the general population. METHODS: Speaking voice profiles with four different intensity levels, hormone concentrations, and anthropometric parameters were assessed for 2,381 individuals aged 40-79 years, who were randomly sampled from the population of a large city in Germany. Multivariate analysis was performed, adjusting for age and stratified by sex. RESULTS: Taller body height was associated with lower frequencies. Higher body weight was associated with lower frequencies and higher sound pressure levels. The ratio of chest to abdominal circumference was associated with the sound pressure levels in males and females: participants with larger breast-to-abdomen-ratio were found to have higher sound pressure levels. Among the sexual hormones, higher concentrations of DHEA-S were associated with lower fundamental frequencies of the voice while using the normal speaking voice. In addition, bioavailable testosterone was associated with the sound pressure level of the normal speaking voice in men and the softest speaking voice in women. CONCLUSION: Our findings suggest that BMI, body height, body weight, breast-to-abdomen-ratio, bioavailable testosterone, and DHEA-S are associated with the speaking voice in adults. No associations between testosterone and the frequency of the speaking voice were found.
Keywords: Adult; Aged; *Anthropometry; Body Height; Body Mass Index; *Body Size; Body Weight; Cross-Sectional Studies; Dehydroepiandrosterone Sulfate/*blood; Estradiol/blood; Female; Follicle Stimulating Hormone, Human/blood; Germany; Humans; Linear Models; Luteinizing Hormone/blood; Male; Middle Aged; Multivariate Analysis; Speech Production Measurement; Testosterone/*blood; *Voice Quality